Ignorance is Bliss? Geographical Knowledge in Herodotus and Thucydides - Clarke, Katherine (Histos, 2019)
This article explores the value attached to geographical knowledge, firstly in the work of Herodotus and then in comparison with a key Thucydidean episode. Having established the desirability of knowledge at least for the historian himself, it considers Herodotean episodes in which the geographical knowledge of characters within the narrative is limited, or even deliberately distorted, not always to their disadvantage. It then places against this backdrop Thucydides’ puzzling account of Athenian ignorance in advance of their ill-fated expedition to Sicily. It proposes that Thucydides exaggerates the Athenians’ lack of geographical knowledge in order to characterise them as tragically overtaken by an irrational desire for the fatal expedition.